Building a community of the sighted people with the blind on the example of Dom Bożego Narodzenia in Niepołomice - Lipiec, Dariusz (HTS teologiese studies, 2024)
The aim of this article is to present how to build a community consisting of the sighted people and of the blind. Dom Bożego Narodzenia in Niepołomice in Poland is an example of such a community, as its members – the sighted people and the blind – form a community modelled on the family. The community was created out of the religious inspiration and its building is in accordance to the Christian values. In order to realise the aim of this article, the author interviewed 10 community members (both the sighted and the blind). The received answers were subjected to quality research. The article presents the teaching of the Catholic Church which concerns the community life of people with disabilities and those fully able-bodied. The next step was to present the characteristics of the residents of the nursing home in Niepołomice. Building the community was presented in two dimensions: vertical and horizontal. The vertical dimension is connected with creating the community with God, and it is inspired by the Christian values in building the family relations. The horizontal dimension is connected with building the human community in its everyday life and in celebrating.Contribution: The research undertaken on the community well-being of people with visual disabilities has shown that such people are able to participate subjectively in building a home community similar to a family with sighted people.